Emotion profiles and their motivational antecedents among adolescent athletes in intensive training settings - Martinent, G.; Gareau, A.; Lienhart, N.; Nicaise, V.; Guillet-Descas, E. (Psychology of Sport and Exercise, 2018)
The purposes of this study were to: (a) identify emotion profiles of athletes involved in an intensive training setting across three measurement points (beginning, middle and end of the season); (b) explore the stability and change of those emotion profiles over the season; and (c) examine if self-determined motivation predicts membership to the emotion profiles. Method: Three hundred and forty-three adolescent athletes in intensive training settings filled out measures of emotions (sadness, anxiety, anger, happiness, confidence, love, harmony, and vitality) and self-determined motivation (autonomous and controlled). Data were analyzed using a latent profile transition analysis (LPTA) approach. Design: longitudinal three-wave design. Results: LPTA results revealed four emotion profiles: High positive emotions (PE) and low negative emotions (NE), moderately high PE and low NE, moderately high PE and NE, and moderate PE and NE. Individuals exhibited both changes and stability in their emotion profile over time. Membership of emotion profiles were predicted by autonomous and controlled motivation assessed at baseline. Conclusions: The emotion profile approach was proven useful in understanding emotions experienced over time by adolescent athletes involved in intensive training settings and has implications for psychological intervention.